Advanced malignant melanoma during pregnancy: technical description of sentinel lymph node biopsy followed by radical lymph node dissection - Wainstein,Alberto Julius Alves (2015)
Abstract Introduction: melanoma is a very aggressive cancer, with increasing incidence, and is currently the fifth most common cancer in men and the sixth most common in women in the United States. Melanoma is not unusual in pregnancy, with an estimated occur-rence rate of 1:1.000. Although not the most common cancer in pregnancy, melanoma is the tumor with the highest incidence ofplacenta and fetus metastases. Description: a 29-year-old lady, 4 weeks after conception underwent resection of an atypical pigmented lesion after a diagnosis of stage T4b melanoma. At 16 weeks she underwent a broad local excision and sentinel lymph node (SLN) biopsy. SLN was evaluated histologically and tested positive for melanoma. A radical axillary lymphadenectomy was performed on the patient without evidence of metas-tasis in any other LN. In the 40th week of pregnancy, labor was induced and a healthy newborn was deli-vered via cesarean. Discussion: melanoma management in pregnancy is more complex and requires multidisciplinary coor-dination, as well as extensive discussion with the patient and her family. We present a case report description in which treatment recommendations are established according to no pregnancy experience.